THE RELEVANCE OF CHOLESTEROL AND TRIGLYCERIDES IN PREGNANCY - Milinčić, Miloš; Dugalic, Stefan; Gojnic, Miroslava (Medical Research, 2023)
Cholesterol participates in the construction of all body cells, steroid hormones, and bile acids. Its role in pregnancy is of key importance in the form of the synthesis of hormones without which conception and pregnancy would not be possible, and later in developing the physiological functions of the fetus. Triglycerides as the main energy substrate serve in the normal growth and development of the fetus. Normal reference values ​​for lipid status in pregnancy have not yet been established. It has been proven that elevated, as well as reduced values ​​of total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG) participate in pathological conditions of pregnancy - gestational diabetes mellitus, preeclampsia, macrosomia, restricted fetal growth, etc. The treatment of dyslipidemia is limited due to the lack of pharmacological studies on pregnant women, as well as the teratogenic effect of anti-lipid drugs. This review article deals with the effect of cholesterol and triglycerides on pregnancy, pregnancy outcomes, prenatal and postnatal effects on the fetus, as well as current and future treatment options.